Bronchoalveolar lavage fluid microbiota dysbiosis in infants with protracted bacterial bronchitis - Bao, Yanmin; Li, Yinhu; Qiu, Chuangzhao; Wang, Wenjian; Yang, Zhenyu; Huang, Lu; Feng, Xin; Liu, Yanhong; Li, Jing; Zhou, Qian; Wang, Heping; Li, Dongfang; et al. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Protracted bacterial bronchitis (PBB) is a chronic purulent bronchitis which could cause recurrent coughing and wheezing in infants. Based on previous reports, main pathogens which caused PBB were identified in the patients, but their impacts on lung microbiota dysbiosis remain unclear. Methods: In this study, bronchoalveolar lavage fluid (BALF) was collected from PBB infants and tracheomalacia (TM) infants younger than 3 years old under the instruction of Shenzhen Children’s Hospital, and 12 samples were randomly selected for 16S rDNA analysis in each group. Based on the results of bacterial composition, the microbiota diversity and co-occurrence network in PBB and TM group were detected and compared. Results: Microbiota diversity was significantly lower in PBB group than it in TM group (P